Three-dimensional analysis of mandibular and temporomandibular joint morphology and condylar movement in skeletal class II and III patients - Aung Thet Khine; Hideyuki Yoshizawa; Jun J Miyamoto; Jun-Ichi Takada; Atsuhiro Inoue; Keiji Moriyama (Clinical and Investigative Orthodontics)
Purpose This study compared the three-dimensional (3D) morphology of the mandible, temporomandibular joint (TMJ), and condylar movement in skeletal Class II and Class III patients and investigated correlations between morphology and movement in each skeletal pattern.Materials and Methods This study included patients with skeletal Class II (Class II group, n = 23) and skeletal Class III (Class III group, n = 25). Computed tomography was used to perform 3D morphological measurements of the mandible, condyle, articular eminence, joint space, and condylar position. Condylar path length (CPL), sagittal condylar inclination (SCI), and transverse condylar inclination (TCI) during most protrusive mandibular movements were measured using computerized axiography. Each measurement was compared between the two groups using Mann – Whitney’s U test, and the correlation between morphological and movement measurements was examined in each group with Spearman’s rank correlation coefficient.Results The Class II group showed significantly smaller condylar length, ramus height, mandibular body length, and condylar volume, while larger articular eminence height and more anterior condylar position than the Class III group. As for the condylar movement, the Class II group had significantly larger values in CPL and SCI than the Class III group. The Class II group showed a significant correlation between articular eminence inclination and SCI, while the Class III group showed a significant correlation between superior joint space and CPL.Conclusion Patients with skeletal Class II and III exhibited different correlation patterns between TMJ morphology and condylar movement during mandibular protrusive movement.